Precipitating factors of heart failure decompensation, short-term morbidity and mortality in patients attended in primary care. (1st October 2020) - Verdu-Rotellar, José María; Vaillant-Roussel, Helene; Abellana, Rosa; Jevsek, Lea Gril; Assenova, Radost; Lazic, Djurdjica Kasuba; Torsza, Peter; Glynn, Liam George; Lingner, Heidrun; Demurtas, Jacopo; Borgström, Beata; Gibot-Boeuf, Sylvaine; et al.
Abstract: Objective: To evaluate the precipitating factors for heart failure decompensation in primary care and associations with short-term prognosis. Design Prospective cohort study with a 30-d follow-up from an index consultation. Regression models to determine independent factors associated with hospitalisation or death. Setting: Primary care in ten European countries. Patients Patients with diagnosis of heart failure attended in primary care for a heart failure decompensation (increase of dyspnoea, unexplained weight gain or peripheral oedema). Main outcome measures: Potential precipitating factors for decompensation of heart failure and their association with the event of hospitalisation or mortality 30 d after a decompensation. Results: Of 692 patients 54% were women, mean age 81 (standard deviation [SD] 8.9) years; mean left ventricular ejection fraction (LVEF) 55% (SD 12%). Most frequently identified heart failure precipitation factors were respiratory infections in 194 patients (28%), non-compliance of dietary recommendations in 184 (27%) and non-compliance with pharmacological treatment in 157 (23%). The two strongest precipitating factors to predict 30 d hospitalisation or death were respiratory infections (odds ratio [OR] 2.8, 95% confidence interval [CI] (2.4–3.4)) and atrial fibrillation (AF) > 110 beats/min (OR 2.2, CI 1.5–3.2). Multivariate analysis confirmed the association between the following variables and hospitalisation/death: In relation to precipitating factors: respiratory infection (OR 1.19, 95% CI 1.14–1.25) and AF with heart rate > 110 beats/min (OR 1.22, 95% CI 1.10–1.35); and regarding patient characteristics: New York Heart Association (NYHA) III or IV (OR 1.22, 95% CI 1.15–1.29); previous hospitalisation (OR 1.15, 95% CI 1.11–1.19); and LVEF < 40% (OR 1.14, 95% CI 1.09–1.19). Conclusions: In primary care, respiratory infections and rapid AF are the most important precipitating factors for hospitalisation and death within 30 d following an episode of heart failure decompensation. Key points: Hospitalisation due to heart failure decompensation represents the highest share of healthcare costs for this disease. So far, no primary care studies have analysed the relationship between precipitating factors and short term prognosis of heart failure decompensation episodes. We found that in 692 patients with heart failure decompensation in primary care, the respiratory infection and rapid atrial fibrillation (AF) increased the risk of short-term hospital admission or death. Patients with a hospital admission the previous year and a decompensation episode caused by respiratory infection were even more likely to be hospitalized or die within 30 d.